Array-based comparative genomic hybridization analysis of recurrent chromosome 15q rearrangements - Sahoo, Trilochan; Shaw, Chad A.; Young, Andrew S.; Whitehouse, Nathan L.; Schroer, Richard J.; Stevenson, Roger E.; Beaudet, Arthur L. (American journal of medical genetics. Part A, 2005)
Genomic rearrangements of chromosome 15q11‐q13 cause diverse phenotypes including autism, Prader–Willi syndrome (PWS), and Angelman syndrome (AS). This region is subject to genomic imprinting and characterized by complex combinations of low copy repeat elements. Prader–Willi and Angelman syndrome are caused primarily by 15q11‐13 deletions of paternal and maternal origin, respectively. Autism is seen with maternal, but not paternal, interstitial duplications. Isodicentric 15q, most often of maternal origin, is associated with a complex phenotype often including autistic features. Limitations of conventional cytogenetic tests preclude a detailed analysis in most patients with 15q rearrangements. We have developed a microarray for comparative genomic hybridization utilizing 106 genomic clones from chromosome 15q to characterize this region. The array accurately localized all breakpoints associated with gains or losses on 15q. The results confirmed the location of the common breakpoints associated with interstitial deletions and duplications. The majority of idic(15q) chromosomes are comprised of symmetrical arms with four copies of the breakpoint 1 to breakpoint 5 region. Patients with less common breakpoints that are not distinguished by routine cytogenetic methods were more accurately characterized by array analysis. This microarray provides a detailed characterization for chromosomal abnormalities involving 15q11‐q14 and is useful for more precise genotype–phenotype correlations for autism, PWS, AS, and idic(15) syndrome. © 2005 Wiley‐Liss, Inc.